Cooperação internacional e redes metaestáveis: um estudo comparado das políticas de inclusão para as pessoas com deficiência promovidas pela Universidade Estadual da Paraíba e pela Universidade de Romatre - Soares, Christiano Cordeiro (2023)
Inclusion of people with disabilities in higher education is a phenomenon that started timidly in the second half of the 20th century, gaining strength in several countries in the 21st century. In this scenario, this research aims to develop a comparative study of the inclusion policies adopted at the Paraíba State University - UEPB and at the Università Degli Studi Roma Tre - ROMATRE, which create access and permanence conditions for people with disabilities in higher education, based on the United Nations International Convention on the Rights of Persons with Disabilities - CIDPD of 2006 and the SOLIDARIS network. The SOLIDARIS network was formed through a project approved in the educational policy of international collaboration within the framework of the European Union program, Erasmus Plus. Part of this dissertation argues that inclusion policies for people with disabilities only happen through a metastable network, that is, with the perception that policies do not happen in isolation and that it is necessary to build partnerships that consolidate and feed each other. In this scenario, socio-historical-dialectical materialism and comparative study are presented as foundations, based on the following theoretical categories: hegemony, contradiction, metastability, ecology of knowledge, externalization, indigenous foreigner and hybridization; and the empirical categories: access and permanence, in which we reflect on the role of international educational cooperation and the metastable character of social relations that aim to ensure rights and public policies of access and permanence of people with disabilities in higher education in the neoliberal context. With this objective in mind, a critical analytical approach to the institutional work of UEPB and ROMATRE for people with disabilities was used, supported by observation visits and documental analysis of the materials produced by the SOLIDARIS network and the official websites of the Brazilian and Italian institutions. The results show, among other aspects, that the networks of studies on people with disabilities and the recognition of international agreements as a right lead to a double synergistic movement: on the one hand, these studies modify the internal laws of countries towards educational inclusion; on the other hand, international standards are sources of struggle to ensure inclusion policies for people with disabilities. Regarding the implementation of these public policies at UEPB and ROMATRE, higher education institutions, it is considered that even registered in legal and technical documents there are no guarantees that they are feasible, thus understanding themselves as fields of dispute that are activated in metastability.